Pengembangan Nilai Melalui Olahraga: Analisis Bibliometrik Menggunakan Vosviewer - Hidayat, Muhamad Zidane Fahrezi; Ma’mun, Amung; Nugraha, Reshandi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The research aims to analyze bibliometric data and provide a general overview of the literature in sports, especially the development of values ​​through sport or value development through sport. This research discusses the concept of Value Through Sport, which underlines the role of sport in developing social, cultural, and spiritual values. Sport not only provides physical benefits but also shapes individual character and attitudes, such as cooperation, leadership, and discipline. Using bibliometric analysis, this research analyzes data from scientific publications related to the development of values ​​through sport using the VOSviewer application. The research results show a decrease in the number of publications associated with Value Development Through Sport from 2019 to 2024, as well as the identification of 61 relevant key terms. In conclusion, the network visualization shows relationships between research topics that highlight the importance of sport in building values ​​and character, as well as the potential for further research on topics that are still rarely researched. Keywords: Bibliometric Analysis, Value Development, Sport